The birth of science : ancient times to 1699 - Spangenburg, Ray, 1939-; Moser, Diane, 1944-; Spangenburg, Ray, 1939- (New York : Facts on File, 2004)
Discusses major scientists as well as scientific knowledge and discoveries from ancient times through the seventeenth century
Rev. ed. of: The history of science from the ancient Greeks to the scientific revolution, 1993
Keywords: Science -- History -- Juvenile literature; Science -- History